Tradição gloriosa: Lyceu Parahybano, uma história de protagonismos (1886-1923) - Miranda, Itacyara Viana (2017)
This thesis has to discuss the Lyceu Parahybano in the late 19th century to the early decades of the twentieth century, being the initial landmark in 1886 when it was formulated a new Internal Regulations of the institution and in 1923 the final mark, regarded as the termination of a restructuring cycle, glory decades, of that space of the public secondary education. The timeframe has been designed taking into account the existence of an external transition – change the system of Monarchy government to Republic – and internal transition-pedagogical and physical structure of the school. The proposal was to grasp how Lyceu, through the actions of their instructional subjects developed elements of a political role, social, cultural and educational in Paraiba. Involved in a network of various relationships the institution established with the community living spaces that extended beyond its limits. In this sense, we have taken into account not only what produced internally, but also their interactions with the city, its presence in journalistic writings, among other factors. The work pointed to the debate of a memory built by and for that education environment that was anchored in the likely strength of the institution by the society. The work pointed out to the debate of a memory built by and for that education environment that was anchored in the likely strength of the institution by the society. For the theoretical methodological support, we used Justin de Magalhães (2004), to understand the school/educational institution; René Rémond (2003) and Motta (2009), in spite of the political cultures; Roger Chartier (2002), for the idea of representation. The specific historiography of the Lyceu, we announced Menezes (1982a) and Ferronato (2012) as points of discussion. With regard to the documentary corpus we had the support of: regulations, statutes, laws, decrees, presidential reports, newspapers and magazines, the example of the New Era. All this material helped us to apprehend the Lyceu Parahybano as an educational space, but also of political and cultural interests. Location of intellectual training and citizens principles, of individual and collective memories that credited the institution hope of better days for the State